The Assessment of Patient Safety Culture Among Doctors, Nurses, and Pharmacists in a Public Hospital in Indonesia - Baiq Khuwailidia Kartikasari; Samirah Samirah; Elida Zairina, S.Si., MPH., Ph.D., Apt. (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Understanding the patient safety culture is one step toward improving patient safety. Patient safety culture is the main foundation of patient safety arrangements that aim to improve the quality of service of healthcare facilities by implementing risk management in all service areas. This study aimed to determine the cultural picture of patient safety among health workers in a public hospital in East Lombok. This study was observational and cross-sectional, using the Hospital Survey of Patient Safety Culture (HSOPSC) questionnaire from the Association of Health Care and Research Quality (AHRQ.) The population of this study was healthcare professionals (doctors, dentists, pharmacists, pharmaceutical technical personnel, nurses, and midwives) at Dr. R. Soedjono Selong Hospital in East Lombok. Descriptive and inferential statistics were used to adjust frequency distribution tables to identify variable relationship differences. The results analysis followed the guidelines from AHRQ, and univariate analysis was carried out. Among the 250 employees invited to participate, 238 (95.2%) completed the surveys. The dimension with the highest percentage of positive responses was an organizational learning-continuous improvement (91.3%), and the dimension with the lowest positive responses was staffing (42.5%). Generally, the patient safety culture in health workers at Dr. R. Soejono belongs to the strong culture (70.34%). Hospital management needs to improve and evaluate dimensions with a low positive response. Building a strong patient safety culture is essential to enhance the quality of service. Creating a positive safety culture for patients is unavoidable by taking steps that support all dimensions of the safety culture.